2015
DOI: 10.1074/jbc.m114.635144
|View full text |Cite
|
Sign up to set email alerts
|

Human CHAC1 Protein Degrades Glutathione, and mRNA Induction Is Regulated by the Transcription Factors ATF4 and ATF3 and a Bipartite ATF/CRE Regulatory Element

Abstract: Background: CHAC1 is associated with the stress response in atherosclerosis. Results: ATF4, ATF3, and CEBP␤ regulate CHAC1 transcription. Human CHAC1 protein overexpression depletes glutathione. Conclusion: CHAC1 is induced following multiple cell stress signals and leads to depletion of glutathione. Significance: CHAC1 may be an essential link between stress signaling and the oxidative status of the cell, contributing to multiple diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
141
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(165 citation statements)
references
References 45 publications
4
141
0
Order By: Relevance
“…Recently, Chac1 was reported to function as a γ-glutamyl cyclo-transferase (GGCT) that catalyzes conversion of glutathione (GSH), a tripeptide thiol antioxidant (γ-Glu-Cys-Gly), to 5-oxyProline and Cys-Gly (49, 50). Since Chac1 was highly up-regulated in Lop/+ lenses we predicted that GSH levels may be depleted as a consequence of GGCT activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Chac1 was reported to function as a γ-glutamyl cyclo-transferase (GGCT) that catalyzes conversion of glutathione (GSH), a tripeptide thiol antioxidant (γ-Glu-Cys-Gly), to 5-oxyProline and Cys-Gly (49, 50). Since Chac1 was highly up-regulated in Lop/+ lenses we predicted that GSH levels may be depleted as a consequence of GGCT activity.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al showed the overexpression of CHAC1-caused GSH depletion in mammalian cells [41]. Crawford et al revealed that overexpression of CHAC1 led to a large decrease in total GSH, which was alleviated in a CHAC1 catalytic mutant in HEK293 cells [42]. Therefore, CHAC1 expression is associated with GSH metabolism; CHAC1 plays a critically important role in the process of melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the higher multicellular eukaryotes, two ChaC homologues are present, ChaC1 and ChaC2. Although the mouse and human ChaC1 function as glutathione-degrading enzymes (10,19), the function of the mammalian ChaC2 proteins has not been explored.…”
mentioning
confidence: 99%